Legal Guarantees for the Protection of the Principle of Social Justice (A Comparative Study) - Raad Faleh, Researcher.Shahad; Zaki Nouri, Assist.Prof. Suha (Basra studies journal, 2024)
The principle of social justice has gained significant importance in recent times. Achieving social justice and protecting its principles have become key demands of the people and objectives of modern constitutions, declarations, and international treaties. The principle of social justice represents the common goal of various economic systems and serves as the fundamental pillar of all economic and social rights. Consequently, most modern constitutions and international efforts have focused on establishing the necessary legal rules to provide constitutional and legal guarantees for its protection. This is because such protection results in positive outcomes that enhance the social and economic status of a nation's citizens, leading to political stability and economic growth.